Effect of ageing time on beef quality of rustic type and rustic X Charolais croábreed catle slaughtered at the same finishing grade - Vieira, C.=700 1 Garcia Cachan, M.D.; Recio, M.D.; Dominguez, M.; Sañudo, C.
(Es, En)
ilus., 58 ref.
Keywords: GANADO BOVINO; CRUZAMIENTO; MADURACION; CARNE DE RES; TEXTURA; ESPAÑA